High levels of FSH before puberty are associated with increased risk of metabolic syndrome during pubertal transition. Issue 8 (28th February 2022) - Aydin, Banu Kucukemre; Stenlid, Rasmus; Ciba, Iris; Cerenius, Sara Y.; Dahlbom, Marie; Bergsten, Peter; Nergårdh, Ricard; Forslund, Anders
Summary: Background: During perimenopause, the rise in serum follicle‐stimulating hormone (FSH) is associated with increased adiposity, insulin resistance (IR), and metabolic syndrome (MetS). However, data for the pubertal period, which is characterized by increasing FSH levels and changing body composition, are limited. Objectives: To investigate the relationships between FSH and anthropometric changes, IR markers, and development of MetS in the peripubertal period. Methods: Uppsala Longitudinal Study of Childhood Obesity (ULSCO) is an ongoing study that aims to understand the factors contributing to childhood obesity and the development of obesity‐related diseases. We analysed the subset of participants who were prepubertal at the first visit (n = 95, 77 with obesity). Mean follow‐up time was 3.0 ± 1.4 years. Results: Higher serum FSH levels at the first visit were associated with an increased likelihood of elevation in body mass index (BMI SDS) (p = 0.025, OR = 16.10) and having MetS (p = 0.044, OR = 4.67) at the follow‐up. We observed nonlinear relationships between varying serum FSH levels and markers of adiposity and IR, especially in girls. At the first visit, when girls were prepubertal, FSH was negatively associated with BMI (β = −0.491, p  = 0.005) and positively associated with sex hormone‐binding globulin (SHBG) (β = 0.625, p  = 0.002). With the progression of puberty, negative associations between BMI and SHBG disappeared while FSH became positively associated with HOMA‐IR (β = 0.678, p  = 0.025) and fasting insulin (β = 0.668, p  = 0.027). Conclusions: Higher serum FSH levels in prepubertal children were associated with an increased risk of MetS development during pubertal transition. Along with nonlinear associations between varying serum FSH levels and IR markers, our results might imply a relationship between FSH and IR of puberty.